Analysis of the Impact of Child Marriage on Delivery Complications - Nunik Hindrawati; Raden Maria Veronika Widiatrilupi (Health and Technology Journal (HTechJ), 2026)
Child marriage remains a persistent public health issue in Indonesia, including in Jember Regency. Early marriage is closely linked to adolescent pregnancy and may increase the risk of childbirth complications, which contribute to maternal and neonatal morbidity. This study aimed to analyze the association between child marriage (<18 years) and the incidence of childbirth complications. A cross-sectional analytical study was conducted using purposive sampling. The study included 30 mothers who had delivered between January and December 2024 and met the inclusion criteria. Data were obtained from medical records. Age at marriage was categorized as <18 years or≥18 years, and childbirth complications were recorded as present or absent. Data were analyzed using the Chi-square test and logistic regression. Of the total respondents, 2 mothers married before age 18, and 28 married at age 18 or older. Childbirth complications occurred in 1 out of 2 mothers (50.0%) who married before 18 years and in 24 out of 28 mothers (85.7%) who married at ≥18 years. Statistical analysis showed a significant association between age at marriage and childbirth complications (p = 0.042). Logistic regression analysis indicated that age at marriage was associated with the risk of childbirth complications (OR = 5.45). Age at marriage is significantly associated with the incidence of childbirth complications. These findings highlight the importance of preventing child marriage, strengthening reproductive health education, and improving the quality of antenatal care services to reduce maternal and neonatal complications.